AUTOKRITIK PERATURAN MAHKAMAH AGUNG NO. 1 TAHUN 2016 TERHADAP TINGGINYA TINGKAT PERCERAIAN DI PENGADILAN AGAMA SULAWESI TENGGARA TAHUN 2013-2017 - Kamaruddin Kamaruddin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
This study aims to analyze the implementation of mediation in Perma No. 1 of 2016 in Southeast Sulawesi Religious Courts in 2013-2017, the factors causing the high divorce rate, and solutions to minimize the high divorce rate. This type of research is qualitative research, namely library and field research with analytical descriptive methods and philosophical normative approaches. The results of the research concluded that the implementation of mediation in divorce cases of Perma No. 1 of 2016 in the Southeast Sulawesi Religious Courts in the period 2013-2017 was not yet effective, because Perma No. 1 of 2016 can not applied optimally. This is evident from the divorce rate is still relatively high among religious courts. The factors causing the high divorce rate are the husband or wife committing adultery, domestic violence, drinking liquor, low education level, family environment that likes to interfere in husband and wife, inadequate economy the cost of living for the family, the husband migrated to find work without news, so the wife remarried. Efforts made to minimize the high divorce rate in Southeast Sulawesi Religious Courts include maximizing BP4 services before being brought to the Religious Courts, counseling about the consequences of divorce, making it difficult to provide recommendations from superiors, establishing exemplary household systems as the pattern of coaching in the neighborhood RT, RW, rural/urban.